Preliminary crystallographic analysis of a double mutant of the acetyl xylo-oligosaccharide esterase Axe2 in its dimeric form - Lansky, Shifra (International Union of Crystallography, 2014)
Xylans are polymeric sugars constituting a significant part of the plant cell wall. They are usually substituted with acetyl side groups attached at positions 2 or 3 of the xylose backbone units. Acetylxylan esterases are part of the hemicellulolytic system of many microorganisms which utilize plant biomass for growth. These enzymes hydrolyze the ester linkages of the xylan acetyl groups and thus improve the accessibility of main-chain-hydrolyzing enzymes and their ability to break down the sugar backbone units. The acetylxylan esterases are therefore critically important for those microorganisms and as such could be used for a wide range of biotechnological applications. The structure of an acetylxylan esterase (Axe2) isolated from the thermophilic bacterium Geobacillus stearothermophilus T6 has been determined, and it has been demonstrated that the wild-type enzyme is present as a unique torus-shaped octamer in the crystal and in solution. In order to understand the functional origin of this unique oligomeric structure, a series of rational noncatalytic, site-specific mutations have been made on Axe2. Some of these mutations led to a different dimeric form of the protein, which showed a significant reduction in catalytic activity. One of these double mutants, Axe2-Y184F-W190P, has recently been overexpressed, purified and crystallized. The best crystals obtained belonged to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 71.1, b = 106.0, c = 378.6 Å. A full diffraction data set to 2.3 Å resolution has been collected from a flash-cooled crystal of this type at 100 K using synchrotron radiation. This data set is currently being used for the three-dimensional structure analysis of the Axe2-Y184F-W190P mutant in its dimeric form.